Differences in anthropometric characteristics and motor abilities of professional football players from leading and average teams in Serbian super league - Radakovic, R.; Majkic, B.; Katanic, B.; Govindasamy, K.; Veljkovic, A. A.; Baltean, A. I.; Geanta, V. A. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Aim of study The aim of the study was to examine the differences between professional football players from leading and average teams in anthropometric characteristics and motor abilities. The sample of participants included 55 professional football players from the Serbian Super League, the top-tier national football competition.